(untitled) (Research, Society and Development, 2021)
Several studies have discussed the benefits and safety strategies for resistance training in children and adolescents, however, their inclusion in school physical education classes is still not significant. The analysis of the current scientific evidence on resistance training in schoolchildren can broaden the understanding of their pedagogical action and allow insertion of this content in school. In this sense, this review study aimed to synthesize the evidence on resistance training in schoolchildren. The electronic databases consulted were BVS, PUBMED and SCIELO, using the combination of terms related to resistance training, adolescents and school. The mapping resulted in 08 articles, including field research and reviews, published between 2010 and 2020. The results showed an improvement in physical fitness, body composition and biochemical variables, a reduction in postural deviations and the risk of injuries, as well as diseases associated with sedentary lifestyle, in addition to increasing the motivation and adherence of students in physical education classes. These results indicate that resistance training, when under adequate supervision, can promote numerous benefits and increase students’ motivation.